Microcirculation in Hypertension: An Update on Clinical Significance and Therapy - Tsioufis, Costas; Dimitriadis, Kyriakos; Katsiki, Niki; Tousoulis, Dimitris (Current Vascular Pharmacology, 2015)
Essential hypertension is closely related to alterations of the microcirculation as evidenced by increased media-to-lumen ratio of small resistance arteries and capillary rarefaction. It has been proposed that microvasculature alterations can further deteriorate target organ damage under the influence of increased hemodynamic load in hypertension. More than a decade ago, small artery structure was found to be the most potent predictor of cardiovascular events in essential or secondary hypertension. Amelioration of resistance vessel structure by antihypertensive drugs showed a clear benefit when patients were treated with calcium antagonists and renin-angiotensin-aldosterone inhibitor regimens. Well-designed controlled studies are needed to address the important questions whether different antihypertensive agent combinations could be related to diverse microcirculatory “responses” in terms of structure and function.
Keywords: cardiovascular events